1980
DOI: 10.1210/endo-107-6-2099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Streptozotocin Diabetes on the Hypothalamic-Pituitary-Thyroid Axis in the Rat*

Abstract: Studies of the hypothalamic-pituitary-thyroid axis have been performed in streptozotocin (STZ)-diabetic Wistar rats and their controls. Plasma PBI concentration, plasma and pituitary TSH, contents, and hypothalamic TRH content were measured by RIA in basal and stimulated conditions. Compared to controls, rats made diabetic by 6.0 or 7.5 mg STZ/100 g BW showed decreased plasma PBI and TSH and diminished pituitary TSH content, with greater alterations in rats receiving the highest STZ dose. Both diabetic groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1
1

Year Published

1983
1983
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 11 publications
2
39
1
1
Order By: Relevance
“…Absolute thyroid and pituitary gland weights were unchanged in all 3 DM groups, in contrast to a significantly decreased thyroid or pituitary gland weight reported previously (17,18) for male Wistar rats 15 days after DM induction. This difference may be related to the different sex or strain of the animals studied.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Absolute thyroid and pituitary gland weights were unchanged in all 3 DM groups, in contrast to a significantly decreased thyroid or pituitary gland weight reported previously (17,18) for male Wistar rats 15 days after DM induction. This difference may be related to the different sex or strain of the animals studied.…”
Section: Discussioncontrasting
confidence: 85%
“…Several investigators have reported decreased serum TSH as well as T 4 levels 10 to 30 days after DM induction (1)(2)(3)17,18). The decreased TSH has been ascribed to a diminished pituitary sensitivity to TRH (17,19) or to an intrinsic reduction in the constitutive and/or regulated TSH secretion by the diabetic thyrotropes (20).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to glucocorticoids, the hypothalamo-pituitary-thyroid axis is regulated by insulin. Rats that were made insulin deficient by the administration of streptozotocin showed decreases in circulating levels of TSH, T3 and T4 as well as pituitary TSH and hypothalamic TRH content (Gonzalez et al, 1980 andMitsuma andNogimori, 1982). Thus, it is unlikely that the hyperinsulinemia observed after acute (this study) and chronic (Baran et al, 2002) ICV NPY but not HS014 administration in pair fed rats could contribute to the differences in effects on thyroid hormone concentrations presently observed, in keeping with the observation that insulin administration is unable to prevent the fasting-induced reduction in thyrotropic axis in rats .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, corticosterone and insulin status can have significant effects on thyroid hormone concentrations (Kakucska et al, 1995, Alkemade et al, 2005, Nicoloff et al, 1970, Gonzalez et al, 1980and Mitsuma and Nogimori, 1982. Therefore, in order to determine whether changes in insulin or corticosterone levels may have contributed to these changes in thyroid hormone concentrations, we investigated circulating insulin and corticosterone concentrations in NPYand HS014-injected rats.…”
Section: Acute Central Npy But Not Hs014 Injection Decreases Circulatmentioning
confidence: 99%
See 1 more Smart Citation